When Predictive Mechanisms Go Wrong: Disordered Visual Synchrony Thresholds in Schizophrenia - Lalanne, Laurence (Oxford University Press, 2012)
Patients with schizophrenia display an impaired sense of temporal continuity, and we showed that they judge events as being simultaneous even in case of large onset asynchronies. We check here whether this means a fusion of events in time, or on the contrary, a segregation of events and a deficit in coding time-event structure. Subjects decided whether 2 squares were displayed simultaneously or asynchronously on the screen and gave their response by hitting a left or right response key. The implicit processing of asynchrony was explored by means of the Simon effect, which refers to the finding that manual responses are biased to the side of the stimulus. We checked whether responses were biased to the side of the first or second square, when squares were asynchronous and displayed on opposite sides. Results revealed an enlarged time window in patients irrespective of the squares’ position (intra- vs interhemispheric presentation). But for asynchronies eliciting “synchronous” judgments, patients’ responses were biased to the side of the first square. In contrast, controls were biased in all cases to the side of the second square. The inverse effects observed below thresholds in patients and controls cannot be attributed to a generalized deficit. In controls, elementary predictive mechanisms would allow anticipation of upcoming events, whereas patients appear to process squares as if isolated rather than following each other. Predictive mechanisms would be impaired in patients, who would rather rely on reactive mechanisms in order to perceive asynchrony.